PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIB SDN 007 RAMBAH KABUPATEN ROKAN HULU - Junaidi S '; Titi Solfitri; H. Zuhri D ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. The research was conducted in the sixth grade in second semester of academic year 2014/2015, in the first cycle of action is refers to measure the implementation of cooperative learning NHT structural approach, further in second cycle, the action taken is based on the reflection of the first cycle. Each cycle has four statges were sequenced are: planning, implementation, observation, and reflection. From the data analysis of students’ mathematics learning outcomes, is an increase in students’ mathematics learning outcomes both in the first and the second cycle. In the first cycle the learning outcomes increased by 23,81% from the the base value before implementation measures. However, in the first cycle the percentage of students who reached the KKM is still beloq 75% so that researchers are trying to fixed the learning process by coninuing the action in the second cycle. In the second cycle also applied cooperative learning NHT, structural approach. Clasically, the students’ test socers who reached KKM in the second cycle increased by 19.05% from the students’ test score in cycle I. Based on the data analysis that obtained during the research and discussion in chapter IV, it conclude that the implementation of cooperative learning structural. Approach numbered heads together (NHT) can improve the students’ mathematics learning outcomes in clas VI.B SDN 007 Rambah Kabupaten Rokan Hulu of academic year 2014/2015 on the basis competence simplify and sort the fractions, convert the fractions form to decimal form.Keywords: Mathematics learning outcome, Cooperative learning, Numbered Heads Together